Pelatihan Pembinaan Ketahanan Keluarga Bagi Dharma Wanita Kabupaten Pangkep - Hasbahuddin; Aztri Fithrayani Alam; Salmiati (Ilin Institute, 2020)
The Purpose Community service activities carried out to provide an understanding of family resilience and how family counseling services play a role in helping to create family security. Activity methods include, 1) preparation, 2) implementation, and 3) evaluation and mentoring. The results of this activity can be concluded that a) provide a new understanding of dharma Wanita mothers in building family resilience, their roles and functions in the family and utilize family counseling services, b) make a positive contribution to adolescents and are able to open new insights into the functions and roles in building resilience family, c) socializing the existence of family counseling guidance services and straightening understanding of the existence of these services, d) providing opportunities for individuals to improve character according to the competencies needed as a family member, e) emerging new abilities in psychosocial aspects that have been underdeveloped so far